Replacement depth and lifespan prediction of enhanced bioretention media under TSS impact conditions - Jiang, Chunbo (Environmental technology, 2025)
The enhanced bioretention system provides a new way to solve the problems of stormwater management brought by urbanization. The knowledge on effects of media modification and long-term operation is scattered, so clogging interaction function, clogging time and depth are analysed to uncover the underneath. River sand, loess, and compost were used as basic fillers, and air-dried water treatment residual (WTR) and recycled aggregate from construction waste (RACW) were used as modifiers to formulate mixed fillers, and synchronized observation of the change rule of hydraulic conductivity and porosity of vertical layering. The study found that the infiltration coefficient of each system tended to decay gradually from top to bottom as the influent TSS accumulated. A set of improved media clogging process prediction framework has been proposed, using rainfall conditions in Northwest China as input conditions, the system clogging time is about 5.5∼7.1 years and the depth of replacement is about 35 cm based on the principles of cake filtration and deep filtration. The results can further understand the function variation of bioretention system under TSS impact conditions, which is helpful to the prediction of the operating life of the system and the evaluation of media replacement depth